2012
DOI: 10.1007/s10903-012-9730-3
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in Perinatal Mortality Rates Among Immigrant and Native Population in Spain, 2005–2008

Abstract: We compared perinatal mortality rates (PMRs) and the risk from certain causes among immigrant and native population in the Valencian Community (Spain). Using data from the Perinatal Mortality Registry, crude and age standardized mortality ratios were obtained in the different groups of mothers. Mortality rate ratios were calculated to compare the causes of death resulting from prematurity, congenital anomalies, infectious diseases and Sudden Infant Death Syndrome between Spanish and foreign women. PMRs were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…Several studies have examined this question and have found that longer US residence is associated with increased risk of obesity in US immigrants. 16,3840 Some studies have focused on Asian populations, but have relied on nationally representative datasets, making it challenging to stratify by country of origin. 16 Aggregated analyses in Asians may mask any heterogeneity that exists among the different ethnic populations.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined this question and have found that longer US residence is associated with increased risk of obesity in US immigrants. 16,3840 Some studies have focused on Asian populations, but have relied on nationally representative datasets, making it challenging to stratify by country of origin. 16 Aggregated analyses in Asians may mask any heterogeneity that exists among the different ethnic populations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite efforts to raise awareness and educate the public about HIV, lack of understanding and stigma associated with HIV still exist (Bova, Nnaji, Woyah, & Duah, 2014; Kinsler, Wong, Sayles, Davis, & Cunningham, 2007; Stangl, Lloyd, Brady, Holland, & Baral, 2013). Stigma can affect PLHIV through harmful overt acts of malice and discrimination from others, and internalized thoughts of being different or inferior because of one’s HIV status (Sayles, Wong, Kinsler, Martins, & Cunningham, 2009).…”
Section: Sensitivity and Privacy Regarding Hiv Status In Rehabilitatimentioning
confidence: 99%
“…Post-deportation, migrants experience multiple social, emotional, and economic stressors that impact their physical and mental health (Pinedo, Burgos, & Ojeda, 2014). Two recent studies conducted among deported migrants in the US-Mexico border region suggest that deportees display an elevated prevalence of depressive symptoms and mental health problems as compared to the general population and migrants without a history of deportation (Bojorquez, Aguilera, Ramírez, Cerecero, & Mejía, 2014; Bojorquez, Mejia, Aguilar, Cerecero, & Albicker, 2014). Similarly, another study conducted among 9,542 migrants on the US-Mexico border in 2014 that compared voluntary-returned migrants with migrants deported from the US found that deportees had 5.52 the adjusted odds of reporting more than one emotional symptom (Fernández-Niño et al, 2014).…”
Section: Introductionmentioning
confidence: 99%